2015
DOI: 10.1111/bpa.12281
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Infections of CNS: Avian Influenza A Virus, Rift Valley Fever Virus and Human Parechovirus

Abstract: History is replete with emergent pandemic infections that have decimated the human population. Given the shear mass of humans that now crowd the earth, there is every reason to suspect history will repeat itself. We describe three RNA viruses that have recently emerged in the human population to mediate severe neurological disease. These new diseases are results of new mutations in the infectious agents or new exposure pathways to the agents or both. To appreciate their pathogenesis, we summarize the essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 118 publications
(182 reference statements)
1
26
0
1
Order By: Relevance
“…While the overall mortality rate for severe RFVF infections is < 1 %, it may approach 50 % in hemorrhagic cases. Neuropathologic findings include diffuse perivascular infiltrates of lymphocytes and macrophages, multifocal meningitis, and focal areas of neuronal necrosis and aggregates of macrophages, lymphocytes, and neutrophils throughout all regions of the brain [79].…”
Section: Bunyaviridaementioning
confidence: 99%
“…While the overall mortality rate for severe RFVF infections is < 1 %, it may approach 50 % in hemorrhagic cases. Neuropathologic findings include diffuse perivascular infiltrates of lymphocytes and macrophages, multifocal meningitis, and focal areas of neuronal necrosis and aggregates of macrophages, lymphocytes, and neutrophils throughout all regions of the brain [79].…”
Section: Bunyaviridaementioning
confidence: 99%
“…Nipah virus, identified in 1998, is emerging zoonosis that affects both animals and humans [13,[21][22][23][24]. Rift Valley fever is a viral zoonosis that was first identified among sheep on a farm in the Rift Valley of Kenya [25][26][27][28][29]. The WHO committee listed another three pathogens/infectious diseases and considered them as serious and require an action as soon as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review using Pubmed, Google Scholar and Scopus showed that bibliometric studies on SARS or Ebola or Nipah virus have been carried out, but as a single disease and not as a group of diseases with potential future severe epidemics [25][26][27][28][29]. The collective analysis of literature on top eight pathogens will give a more comprehensive view on these infectious diseases and will help identify which one needs to be given top priority for funding and research.…”
Section: Introductionmentioning
confidence: 99%
“…Limits of detection, reproducibility, consistency in the brain regions that are analysed and patient-to-patient variability all contribute to the challenges and dangers of ascribing neurotropic infections to be the aetiologic causes of poorly understood CNS diseases. Moreover, the association of 'new' viruses with CNS disease (including Zika virus, which is linked to microcephaly 108,109 ) or the emergence of more neurovirulent influenza strains 110 are reminders that our understanding of the pathogenic consequences of CNS infections remain quite primitive. Translational studies have provided insights into the links between infections and disease but are not without controversy.…”
Section: Perspectivesmentioning
confidence: 99%